Prevent Fraud Criminal Acts to Perform the Maintenance of Public Order and Security in the Area of Law of Demak’s Resort Police - Maulana, Maulana (Advances in Police Science Research Journal, 2024)
This writing is motivated by reports of criminal acts of fraud at the Demak Police Station which are still very high when compared to other reported crimes. Through visiting activities it is hoped that it can reduce criminal acts of fraud in the jurisdiction of the Demak Police. The concepts and theories that the authors use are the concept of effort, namely the concept of visits, the concept of deception, the concept of Bhabinkamtibmas, process management theory, communication theory, and SWOT analysis. The writing method uses a qualitative approach whose results are strengthened by the results of observations, document studies, and results of interviews. The techniques used for data analysis include data collection, data reduction, data presentation, and drawing conclusions. The writing results show that: 1) There is no daily and weekly activity plan; 2) There is still Bhabinkamtibmas which has concurrent duties; 3) Bhabinkamtibmas did not carry out all stages of the visit properly; 4) Bhabinkamtibmas is not supported by auxiliary media in delivering material.